Clinical predictors of admission in infants with acute bronchiolitis. Issue 7 (21st February 2011) - Marlais, M; Evans, J; Abrahamson, E
Abstract : Background: Bronchiolitis is a significant cause of acute morbidity in the first 12 months of life and some infants with bronchiolitis are admitted to hospital. No studies have yet devised a scoring system to predict admission for routine use in the emergency department. Aim: To identify clinical predictors of hospital admission in infants with acute bronchiolitis and to devise a simple clinical risk scoring system which could be used to aid decision making in the emergency department. Methods: All infants presenting with acute bronchiolitis to a dedicated paediatric emergency department from April 2009 to March 2010 were included in the study. Clinical predictors of admission were determined through case note review and logistic regression analysis. The strongest predictors of admission were assimilated into a simple clinical risk scoring system using widely accepted statistical methods. Results: 449 infants presented with acute bronchiolitis during the study period (298 (66%) male, mean age 23±14.5 weeks). 163 (36%) infants were admitted to hospital. The five best predictors of admission (age, respiratory rate, heart rate, oxygen saturations and duration of symptoms) were incorporated into the bronchiolitis risk of admission scoring system. The area under the receiver operator characteristic curve was 0.81 (95% CI 0.77 to 0.85) at the optimal cut-off, demonstrating good diagnostic accuracy. Conclusions: The authors have identified important clinical predictors of admission in acute bronchiolitis. This information has been used to develop a simple clinical risk scoring system to aid decision making in the emergency department.